Animal Intuitions - Kaebnick, Gregory E. (The Hastings Center report, 2016)
As described by Lori Gruen in the Perspective column at the back of this issue, federally supported biomedical research conducted on chimpanzees has now come to an end in the United States, although the wind-down has taken longer than expected. The process began with a 2011 Institute of Medicine report that set up several stringent criteria that sharply limited biomedical research. The National Institutes of Health accepted the recommendations and formed a committee to determine how best to implement them. The immediate question raised by this transition was whether the IOM restrictions should be extended in some form to other nonhuman primates—and beyond them to other kinds of animals. In the lead article in this issue, Anne Barnhill, Steven Joffe, and Franklin Miller consider the status of other nonhuman primates.